An interesting parameter deduced from confirmed infection number in COVID-19 epidemic - Chow CL; Cheng CH; Chow WK (Journal of Medical and Scientific Research, 2023)
In controlling outbreaks of COVID-19, the number of daily confirmed infected cases is useful in deducing parameters to determine emergency management actions such as locking down the cities. However, complicated mathematical models with ordinary differential equations are involved. Resources including manpower and data accessibility are needed. The parameters deduced are always challenged by stakeholders, particularly those from servicing and tourist industry. A simple parameter is proposed to describe the extent of infection by estimating the transient daily infection number divided by the time. The daily infection number in Hong Kong is used to illustrate the approach. This will not require large-scale long-term observation and mathematical modeling or computation.